Buckling prevention of a single long NiTi tube compressive elastocaloric regenerator. (1st June 2023) - Cheng, Siyuan; Xiao, Yinan; Li, Xueshi; Lin, Hongyang; Hua, Peng; Sheng, Liyuan
Graphical abstract: Highlights: A column buckling prevention method for long tubular materials is proposed. The method is validated by stainless-steel tubes and four kinds of outer shells. A 300 mm single-long-tube compressive elastocaloric regenerator is constructed. Temperature span 5.7 K, specific cooling power 150 W∙kg −1, and COP 4.0 are reached. Abstract: Superelastic NiTi tubes have been used in elastocaloric coolers due to the good balance between mechanical stability and heat transfer efficiency, and the tube length increase is crucial to the driving force reduction and total cooling power increase of the coolers. The key challenge to adopt long superelastic NiTi tubes in compressive elastocaloric coolers is to prevent long tubes from buckling. In this article, a buckling prevention method of entraining a single long tubular material into a rigid and thick outer shell was proposed. The enhancement in the maximum compression load of a single long tubular material with an outer shell compared with the bare material was derived using the energy method. The proposed buckling prevention method was validated by compression experiments using a single long stainless-steel tube and outer shells of different materials and outer diameters. The buckling prevention method was successfully applied to a single long polycrystalline superelastic NiTi tube (outer diameter 5 mm, wall thickness 1 mm, and initial length 305 mm) in a layered-structured compressive elastocaloric regenerator. Several stress rise-drop-recover processes due to the friction and sliding of the tube were observed in the training, and the dependences of the stress-strain response of the tube on the applied stress and strain rate were also investigated. An elastocaloric cooler based on the single-long-tube compressive elastocaloric regenerator was constructed and it reached the highest temperature span, specific cooling power, and COP values of up to 5.7 K, 150 W∙kg −1, and 4.0, respectively. The results of the article are significant for developing large-power elastocaloric coolers.